Agenesis Serviks - Meiza Martadinata; Dedy Hendry (Andalas Obstetrics And Gynecology Journal, 2019)
Background : Cervical agenesis is an extremely rare congenital anomaly of female reproductive system with manifestation on the absence of uterine cervix with normal development of uterine and secondary sex signs. According to the American Fertility Society, cervical agenesis is classified as type IB Müllerian anomaly. Symptoms are include primary amenorrhea, cyclic abdominal lower pain and infertility.Objective : To report the treatment of cervical agenesis.Case Report : Reportedly, a woman, 28 years old, came with complaints of primary amenorrhea, cyclic abdominal lower pain and 3 years of primary infertility. From speculum and transvaginal ultrasonography examination, the uterine was slightly smaller than normal, without cervical uterine, found adhesion, both ovarian were normal. Laparoscopic utero-vaginal anastomosis was performed and catheter condom was maintained in the cervical canal for 3 months. Two weeks after catheter was removed, a hysteroscopy was performed, but the canal was found closed.Conclusion : In this case, after the laparoscopic utero-vaginal anastomosis was performed, the cervical canal which has been made, is found closed. So, a further evaluation is needed to get more effective results.Keywords: Type IB Müllerian anomaly, cervical agenesis, primary amenorrhea, infertility, laparoscopic utero-vaginal anastomosis